Self-efficacy, dukungan sosial dan coping stress pada teknisi pesawat di puspenerbal - Bawangun, Hellena Febiola Tesalonika; Warni, Weni Endahing; Marwanto, Tri Budi (Jurnal Psikologi Poseidon, 2024)
This study aimed to investigate how self-efficacy and social support correlate independently and simultaneously with aircraft technician stress coping at the naval aviation center, also known as the aviator center. The saturated sampling technique selected 51 aircraft technicians from the aviation center for this study. We gathered data using scales for social support, self-efficacy, and stress coping, comprising a total of 12 valid items. For data analysis, we applied the product-moment correlation using SPSS version 26 for Windows. The results indicated a significant positive relationship between self-efficacy and social support in managing stress. Additionally, there was a significant positive correlation between self-efficacy in stress management and overall stress coping abilities. Furthermore, the findings demonstrated a significant positive relationship between social support and stress coping. These results provide insights that could inform the development of stress management interventions specifically designed for aircraft engine technicians, particularly those in military settings.